Kesantunan dan Solidaritas dalam Prespektif Komunikasi Lintas Budaya Pada Masyarakat Jawa dan Kei - Prakoso, Imam (SHAHIH: Journal of Islamicate Multidisciplinary, 2019)
This paper aim to describe the form of cross-cultural communication through the politeness and solidarity aspect between the Javanese and Keinese community during the UGM community service program in Kei Islands for July – August 2013. This study conducted using a qualitative method carried out with a case study interpretation approach to investigate forms of cross-cultural communication between UGM community service students as representations of Javanese ethnicity and local residents. The data in this study were collected through direct observation by listening and note-taking techniques while interacting with the local people. The result showed that there are big differences in knowledge of politeness and solidarity between Javanese and Keinese ethnicity. The basic differences are shown by the openness of Keinese people. Strengths and openness of Keinese social ties make the way of their communication become associative and explicit.  Whereas the Javanese people were concern about indirectness, implicit, and always avoiding conflict when they communicate with others. The finding of both cultural types divides into five communication aspects: the way of visiting someone’s house, understanding the concept of time or lexicon of ‘tomorrow’, greetings as convergence strategy, negotiating in the traditional market, and the emotional expression during the talk. However, the phenomenon of cross-cultural communication during the community service program (KKN) in July – August 2013 reflected the openness of Keinese people which represented the pluralism value of its customary law.